Analisis Kompetensi Petugas Rekam Medis dalam Pencapaian Kinerja di Puskesmas Wilayah Kota Bima - Uswatun Hasanah Hasanah; Rizal Pratama Adi Putra (Politeknik Negeri Jember, 2024)
Medical recorders in providing services must be in accordance with competence, based on education and training and are obliged to meet Professional Standards. Education is one aspect that affects the knowledge and understanding of medical recorders in carrying out their duties. Knowledge of medical records will have a major impact on performance as a medical recorder. The purpose of the study was to analyze the competence of PMIK on PMIK performance at the Bima City Health Center. The study used a cross-sectional approach with a sample of 38 medical record officers. Data collection was done by distributing competency and performance questionnaires to all medical record officers in Bima City, data analysis techniques used in this study were chi square test with continuity correction and fisher exact test. The results showed that 44.7% of respondents had high performance and 55.3% had moderate performance. The competency areas of Sublime Professionalism, Ethics and Legal were in the good category (55.3%), Aspects of Introspection and Self-Development in the moderate category (60.5%), Effective Communication in the good category (55.3%), Health Data and Information Management in the good category (50.0%), Clinical Classification Skills, Disease Codification and Other Health Problems, and Clinical Procedures in the moderate category (68.4%), Application of Health Statistics, Basic Epidemiology, and Biomedicine in the moderate category (65.8%) and RMIK Service Management in the good category (73.7%). The results of the analysis found that each area of competence of medical record officers had a relationship with performance (p<0.05). It is important for RMIKs to continuously improve their competencies through continuing education in medical records and self-development through training activities